Complementary and alternative medicine use among people living with HIV in Shiraz, Southern Iran - Mosavat, Seyed Hamdollah; Pasalar, Mehdi; Joulaei, Hassan; Ameli, Vira; Heydari, Seyed Taghi; Mirzazadeh, Ali; Hashempur, Mohammad Hashem (Frontiers in Public Health, 2023)
Background Living with HIV requires lifelong care to support engagement with and adherence to antiretroviral therapy. The Middle East and North Africa region provides access to ART, but research is lacking on the lived-experiences of people living with HIV. Globally, complementary and alternative medicine (CAM) is increasingly used by patients who need support alongside receiving medical treatment for chronic conditions. This study aims to examine the frequency and reasons behind the use of CAM, as well as identify its associated factors among people living with HIV in Shiraz, Iran. Methods In this cross-sectional study, a total of 320 patients (aged 18–70 years) with a confirmed diagnosis of HIV residing in Fars province and diagnosed between 1999 and 2019 were recruited randomly through their clinical record numbers from five HIV treatment centers. They were surveyed on their quality of life and CAM use via the Short-Form Health Survey questionnaire (SF-36) and a semi-structured survey of “CAM use.” The data analysis for this study involved the use of Chi-squared test, independent t-test, and multiple logistic regression model. Results Of 287 patients, 89.22% reported using CAM in the previous year. CAM use was more prevalent among those with a family history of CAM use (94.3% vs. 81.8%, p = 0.023). Frequent reasons for using CAM were reported to be sexual dysfunction (32.4%), depression (28.3%), thirstiness (23.3%), and nausea (17.5%). Quality of life, as measured via the SF-36 questionnaire in all its 8 sub-domains, did not differ among those who used CAM versus those who did not (61.5 ± 27.6 vs. 58.1 ± 30.9, p = 0.626). Conclusion CAM was used among a majority of people living with HIV in Shiraz, Iran. People who used CAM appeared to experience a similar quality of life relative to those who did not use CAM. Future studies on the modalities of engagement with CAM can improve patient-physician shared decision-making and increase lifelong care options for people living with HIV.